2021
DOI: 10.1149/2162-8777/ac3f1d
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Charge Retention of a Non-Volatile Memory by a Bandgap-Engineered Charge Trap Layer

Abstract: In recent years, research based on HfO2 as a charge trap memory has become increasingly popular. This material, with its advantages of moderate dielectric constant, good interface thermal stability and high charge trap density, is currently gaining in prominence in the next generation of nonvolatile memory devices. In this study, memory devices based on a-IGZO thin-film transistor (TFT) with HfO2/Al2O3/HfO2 charge trap layer (CTL) were fabricated using atomic layer deposition. The effect of the Al2O3 layer thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Doping/mixing with other elements was a very efficient way to modify the density and spatial and energy location of electrically active defects. Bandgap engineering of the CTL by introducing Al in HfO 2 or stacking HfO 2 with Al 2 O 3 has been suggested [21][22][23][24], resulting in an enhancement in memory performance and reliability.…”
Section: Charge Trapping Layermentioning
confidence: 99%
“…Doping/mixing with other elements was a very efficient way to modify the density and spatial and energy location of electrically active defects. Bandgap engineering of the CTL by introducing Al in HfO 2 or stacking HfO 2 with Al 2 O 3 has been suggested [21][22][23][24], resulting in an enhancement in memory performance and reliability.…”
Section: Charge Trapping Layermentioning
confidence: 99%
“…HfO 2 as the most studied high-k dielectric has been considered also for application in CT-NVMs because it is a trap-rich material, and the study of You et al [11] revealed that the 2 nm HfO 2 layer has a better charge trapping efficiency than 7 nm Si 3 N 4 . Charge trapping properties of HfO 2 could be substantially enhanced by doping with Al atoms or stacking with Al 2 O 3 [12][13][14][15][16]. The storage characteristics could be further boosted by proper treatments, e.g., annealing steps and UV irradiation [14,17,18].…”
Section: Introductionmentioning
confidence: 99%